PENGARUH KUALITAS PELAYANAN CUSTOMER RELATIONS PRODUK E-COMMERCE TERHADAP LOYALITAS PELANGGAN (Survei Kepada Followers Produk Kecantikan SOCIOLLA di Instagram) - Alifvia Wimbi Wardani (2020)
SOCIOLLA is a digital platform in beauty industry that offers thousands of products distributed from inside and outside country. In order to maintain its existence, SOCIOLLA must improve the quality of its best services by maintaining customer satisfaction in order to continue to be the people's choice in buying beauty products online. The purpose of this study was to determine how much influence of the quality of customer relations services at SOCIOLLA on the level of customer loyalty. The approach used in this research is objective approach or quantitative approach. In this study, researchers did a survey method conducted on SOCIOLLA consumers on Instagram. Based on the results of the regression test, the coefficient results between variable X (service quality) and Y variable (customer loyalty) are positive and significant. Correlation analysis shows the result that variable X (service quality) and variable Y (customer loyalty) have a strong relationship. From the results of the coefficient of determination test, the relationship of customer service to customer loyalty shows a striking result. Based on the results of hypothesis testing, Customer Relations service theory and customer loyalty theory have a significant influence between each independent and dependent variable. Based on the results of research that has been done it can be seen that there is a significant relationship between the effect of service quality on customer loyalty on Instagram at SOCIOLLA.